Penerapan Sistem Pakar untuk Mendiagnosa Penyakit Pencernaan dengan Metode Certainty Factor - Andreas Ariyanto Rangga; Karolus Wulla Rato (Pusat Riset dan Inovasi Nasional, 2025)
Expert systems are one of the fields of artificial intelligence (AI) that seeks to adopt human knowledge into computers, so that computers can solve problems as experts usually do. One of the problems handled by expert systems is diagnosis in the health sector, such as to diagnose early suspicions of human digestive diseases commonly known as digestive disorders. The expert system in this study was created in the form of a Web-based application. The application of an expert system with the certainty factor method is used to diagnose diseases in the human digestive system. Digestive diseases in this application are limited to diarrhea, gastritis, dysentery, gastric tumors (benign tumors of the stomach), and appendicitis (appendix). The application of an expert system for digestive diseases in humans contains information on diseases, symptoms, and follow-up treatment. This application can be used as an alternative media for diagnosing digestive diseases, and can help users predict the disease they are suffering from based on the symptoms experienced by the user. The expert system created using the certainty factor method, which means this method provides information related to the disease into a possibility, namely happening and not happening and not knowing. The system design used to illustrate the creation of an expert system consists of context diagrams and data flow diagrams and ERD (Entity Relationship Diagram)